Unveiling the Enigma of Sellar and Parasellar Pathologies: A Pictorial Essay - Gulati, Anshika (Indographics, 2022)
Sellar and parasellar pathologies often present with nonspecific symptoms. Clinical examination and endocrine studies are useful but cross-sectional imaging is indispensable to characterize and accurately localize the lesion. Magnetic resonance imaging with its multiplanar capability and excellent soft tissue contrast resolution is workhorse in evaluation of sellar and parasellar pathologies. Imaging findings of a broad spectrum of lesions is presented in this article along with anatomy and literature review.
Keywords: magnetic resonance imaging; pituitary; sella turcica